Apollonian and Dionysian Elements in the Folk Music of Arghakhanchi and Gulmi - Ghimire, Ram Prasad (Vox Batauli, 2023)
This article argues that most of the Nepali folk music has a provision of combining both the Apollonian and Dionysian virtues. This kind of integration in Nepali folk music can play a vital role in settling the crude emotional force that is produced by the modern music rooted in the Western way of life. The article also presents some evidence and examples of how the ancient peoples of Nepal managed their cultural music and maintained a balance between the Apollonian and Dionysian aspects of the human mind. Of course, an unsettled emotion produced by Western culture and music is a problem. Nepali folk music remains to be a solution to such a problem.